2011
DOI: 10.1063/1.3553856
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption fine structure and x-ray diffraction studies of crystallographic grains in nanocrystalline FePd:Cu thin films

Abstract: FePd alloys have recently attracted considerable attention as candidates for ultrahigh density magnetic storage media. In this paper we investigate FePd thin alloy film with a copper admixture composed of nanometer-sized grains. [Fe(0.9 nm)/Pd(1.1 nm)/Cu(d nm)]×5 multilayers were prepared by thermal deposition at room temperature in UHV conditions on Si(100) substrates covered by 100 nm SiO2. The thickness of the copper layer has been changed from 0 to 0.4 nm. After deposition, the multilayers were rapidly ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This can be explained by a very small grain size in this sample (approx. 8 nm as calculated using the Scherrer equation 32,33 ), which entails the continuous fluctuation of the magnetic moments of each magnetite cluster related to superparamagnetic effects. In such a case, if the relaxation time of the superparamagnetic particle is greater than the lifetime of the excited nucleus, it experiences an average zero field only and Zeeman splitting cannot be observed.…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…This can be explained by a very small grain size in this sample (approx. 8 nm as calculated using the Scherrer equation 32,33 ), which entails the continuous fluctuation of the magnetic moments of each magnetite cluster related to superparamagnetic effects. In such a case, if the relaxation time of the superparamagnetic particle is greater than the lifetime of the excited nucleus, it experiences an average zero field only and Zeeman splitting cannot be observed.…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…It is worth mentioning, that the model does not take into account the temperature dependencies of the material properties such as absorption, density, specific heat and thermal conductivity, and assumes, that between laser pulses they do not change. The peak temperature of 500 circ C was chosen basing on results of our previous investigations, [9,11,12] which showed that it is the minimum temperature required to induce a diffusion process, and to start transformation from multilayer system into ordered alloy.…”
Section: Pulsed Laser Annealingmentioning
confidence: 99%
“…To reduce the temperature of L1 0 structure formation and to induce (001) texture the FePd alloy was doped with Cu, as it was observed in our previous studies. [11,12] We present here the studies of the laser annealing effect on the structure, surface morphology, grain size and shape of FePdCu thin alloy films.…”
Section: Introductionmentioning
confidence: 99%
“…However, in case of ternary FePd:Cu alloy it is necessary to consider where copper atoms are located in the alloy structure. In our previous studies, about the local structure of the FePd:Cu alloy [35,36], it was shown that Cu atoms substitute both Fe and Pd sites. With the assumption of a random distribution of copper atoms in L1 0 structure the expressions for structure factors change to: Fig.…”
Section: Long-range Chemical Order Parametermentioning
confidence: 99%